2019
DOI: 10.4314/jae.v23i4.17
|View full text |Cite
|
Sign up to set email alerts
|

Actors’ Satisfaction with Poultry Value Chain Approach of the Commercial Agricultural Development Project in Enugu State, Nigeria

Abstract: The study ascertained actors' perception of the poultry value chain approach of the Commercial Agricultural Development Project (CADP) in Enugu State, Nigeria. Seventy-one poultry value chain (PVC) actors constituted the sample for the study. Data were analysed using percentages, charts and mean scores. Results show that all (100%) the service providers provided information on how to use drugs and vaccines. The proportion of producers that reared broiler in 2010 were 51% which attained a peak level of 55.8% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…This suggests that farmers who are the direct beneficiaries of the agricultural innovative research results through the programmes organized by the ADP overtime tends to be outdated in terms of ideas and practices and this often results to low agricultural productivity. This result supports the findings of Udoye, et al (2024) which revealed that only 15.6% of poultry producers indicated that they have linkage with agricultural extension professionals'. Similarly, agricultural extension professionals in the study area engage in minimal collaboration with research institutes' thus, indicating that there is a gap between agricultural extension practitioners and research institutes.…”
Section: Linkage With Institutionssupporting
confidence: 90%
“…This suggests that farmers who are the direct beneficiaries of the agricultural innovative research results through the programmes organized by the ADP overtime tends to be outdated in terms of ideas and practices and this often results to low agricultural productivity. This result supports the findings of Udoye, et al (2024) which revealed that only 15.6% of poultry producers indicated that they have linkage with agricultural extension professionals'. Similarly, agricultural extension professionals in the study area engage in minimal collaboration with research institutes' thus, indicating that there is a gap between agricultural extension practitioners and research institutes.…”
Section: Linkage With Institutionssupporting
confidence: 90%
“…Agriculture emphatically contributed to the Nigerian economy during the pre-colonial, colonial, and post-colonial era. However, its contribution to the growth of the nation's Gross Domestic Product (GDP) has been dwindling in recent times due to over-dependence of successive administrations on oil since its discovery [13,14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, available evidence has shown that CADP has made contributions to the aquaculture sector (Christopher et al, 2017;Udoye et al, 2019). However, actors in these sectors do not belong to any category of SMEs in the respective studied areas.…”
Section: Introductionmentioning
confidence: 97%